PENGARUH KOMUNIKASI TERHADAP LOYALITAS KARYAWAN PADA KANTOR PUSAT PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN INDRAMAYU - Ayu Praga Kartini; Ani Yunaningsih (Holistik Manajemen: Jurnal Manajemen, 2020)
This study aims to find out and analyze; communication, and employee loyalty, the magnitude of the effect of Communication on Employee Loyalty partially at the Head Office of the Regional Water Supply Company (PDAM) of Indramayu Regency. The research method used is descriptive method and verification method. The independent variable is communication while the dependent variable is employee loyalty. Data collection techniques using interviews, library research and questionnaires. The method of analysis uses path analysis, validity and reliability, t test, using SPSS for Windows 21 Version. Based on the research analysis the following results were obtained; communication is in the good category, employee loyalty is in the good category, communication has a significant and positive effect on employee loyalty.